The Torah and Atonement - Goldingay, John (Journal of theological interpretation, 2024)
The "sin offering" in Lev 4 has had a significant role in the development of a doctrine of the atonement. The article considers further what Leviticus means by sin or offense, sin offering or offense offering, mistake, guilt offering or fault offering, stain on the person and on the sanctuary, violation, reparation, ransom or covering or cleansing or atonement, and pardon and forgiveness. It notes how these find expression in Israel’s history and considers how they illumine the significance of the death of Jesus for the Jewish people and for the world. It notes that Leviticus does not talk about wrath, propitiation of God, or substitutionary punishment. It concludes that looking at the death of Jesus in light of its provision, one can see that he dissolved our stain, won a victory over the forces of death embodied in our stain, made reparation to God on our behalf, embodied God’s gracious willingness to carry us in our waywardness, and drew the world to seek God’s pardon, but that God is concerned for justice as well as mercy and can also let his people and the world carry their own waywardness.